2022
DOI: 10.36303/jsava.001
|View full text |Cite
|
Sign up to set email alerts
|

Temporally specific adrenocorticotropic hormone reference intervals for horses in South Africa

Abstract: The month-specific ACTH RIs generated in this study will improve the accuracy of diagnosis and monitoring of PPID in the local equine population. These results highlighted the previously recommended need for seasonal and location-specific RIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In total, 25 publications 41,44–67 and seven abstracts 43,68–73 were identified that provided data on the interpretation of diagnostic test results (Table S4). A summary of the key recommendations is presented in Table 9.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 25 publications 41,44–67 and seven abstracts 43,68–73 were identified that provided data on the interpretation of diagnostic test results (Table S4). A summary of the key recommendations is presented in Table 9.…”
Section: Resultsmentioning
confidence: 99%
“…Four publications 51,56–58 and one abstract 73 were included and revealed that whilst latitude impacts ACTH, there are other factors that also play a role in differences identified between locations. Geographic‐specific reference intervals should be used rather than just latitude‐specific intervals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Uruguay, the history of research and control efforts for anaplasmosis (alongside babesiosis) has been associated with the tick species Rhipicephalus microplus (Miraballes and Riet-Correa 2018). Similarly, the epizootiology and control strategies for anaplasmosis have also been studied extensively in South Africa (Potgieter 1979). In Iran, detection and diagnosis of A. marginale in cattle have been crucial, with several herds having a history of acute anaplasmosis (Noaman et al 2009;Noaman 2013).…”
Section: Historymentioning
confidence: 99%